Peningkatan Minat Membaca Anak melalui Modifikasi Media Pembelajaran Lantai Baca pada Anak Usia Dini - Novita, Novitaria; Evia Darmawani; Melinda Puspita Sari Jaya (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to increase reading interest in Chiqa Smart PAUD children. This type of research is classroom action research with two cycles. Research data through observation, observation and documentation of research subjects are children in group B1, totaling 10 children consisting of 5 boys and 5 girls. The results showed that the development of children's interest in reading in children increased after being given action through modification of the reading floor media that supports and children are free to choose and play so as to provide opportunities for children to understand and can foster children's interest in reading from an early age. This increase can be seen from the initial condition of the development of interest in reading. Group B1 children are in the criteria of not developing in cycle 1 with a percentage of 55% increasing to developing very well by taking action using modified reading floor media with children free to choose their own type of play to increase in cycle II with a percentage of 80%, where the modified reading floor media is made more interesting and fun and supports the criteria for developing very well. The children are able to ask questions and answer the explanation given, understand the articulation of letters clearly, correctly mention the initial letters of the picture, are able to read the letters that the children have arranged, mention the signs (the initial letters of the word), are able to tell stories and understand the contents of the story.